THE REALITIES RELATED TO THE LIVING CONDITIONS OF UNISA’S UNDERGRADUATE STUDENTS RESIDING IN SUNNYSIDE, TSHWANE - Alpaslan, Assim Hashim (Social Work/Maatskaplike Werk, 2010)
In its 2015 strategic plan: an agenda for transformation (2006:7), one of Unisa’s mission statements is articulated as follows: “[to] address the needs of a diverse student profile by offering relevant student support, facilitated by appropriate information and communication technology”. In an effort to make this mission statement a reality, a logical point of departure is to answer the following question: “What are the needs of students enrolled at Unisa?”